ANALISIS FAKTOR PENYEBAB SISWA LAMBAN BELAJAR DI KELAS IV SDN PETIR 3 KOTA TANGERANG - Adinda Bilqis Azizah; Rahmawati Eka Saputri; Sri Haryati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to analyze the learning of slow learners and find out the causes of slow learning among students in the class IV B SD Negeri Petir 3 Tangerang city. This study uses a descriptive qualitative approach with data collection methods of observation, interviews, questionnaires and documentation. The results of the analysis in this study showed that there were three slow learners in class IV B SD Negeri Petir 3 Tangerang city. The three slow learners in learning activities often lag behind their friends, getting grades below the Minimum Completeness Criteria (KKM), more passive, less focused when the teacher explains the material, and difficulties in memorizing and understanding. This is because the cognitive slow learning students are limited, so that every time they work on a problem given by the teacher, the answers are not in accordance with the questions and are filled in as best they can. This makes it difficult for teachers, because they do not only focus on students with special needs but also regular students. There are factors that cause the three students to learn slowly in class IV B namely Poverty factor and Parental Intelligence Factor.